Adhesive composition, adhesive, adhesive sheet and laminate

By using the adhesive combination of (methyl) acrylic polymers and ionic compounds to form a adhesive that is intended to be associated with the structure of the integrated association, it solves the problem of decreased energy storage modulus of adhesive layer under high temperature and high humidity conditions. The paragraph follow -up and the optical uneven suppression.

CN115516054BActive Publication Date: 2025-01-28LINTEC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180032463.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-07
Filing Date
2021-03-19
Publication Date
2025-01-28
Estimated Expiration
2041-03-19

AI Technical Summary

Technical Problem

In the prior art, the energy storage modulus of the adhesive layer is excessively reduced under high temperature and high humidity conditions, resulting in problems of bubbles and optical unevenness near the segment difference.

Method used

Adhesive combinations containing (methyl) acrylate polymers and ionic compounds are used to form an intersection -associated structure through the interaction of carbonate ethyl structure and ionic compounds to improve the internal agglomeration and stress relaxation of the adhesive.

Benefits of technology

The segmented follower of the adhesive layer is excellent under high temperature and high humidity conditions, which inhibits the occurrence of uneven optics, and improves the productivity of adhesive slices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115516054B_ABST
    Figure CN115516054B_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive composition containing a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) contains an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer. The adhesive layer obtained from the adhesive composition has excellent step tracking properties and can suppress the occurrence of optical unevenness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition, an adhesive, an adhesive sheet, and a laminate that are suitable for use in a display (display) or the like. Background Art

[0002] In recent years, various mobile electronic devices such as smartphones and tablet computer terminals have displays using display modules, and the display modules have liquid crystal elements, light-emitting diodes (LED elements), organic electroluminescent (organic EL) elements, etc., and such displays are increasingly becoming touch panels.

[0003] In the above-mentioned display, a protection panel is usually provided on the front surface side of the display module. With the thinning and lightening of electronic devices, the protection panel is gradually changing from the conventional glass plate to a plastic plate such as an acrylic plate or a polycarbonate plate.

[0004] At this time, a gap is provided between the protection panel and the display module, so that even when the protection panel is deformed by an external force, the deformed protection panel will not hit the display module.

[0005] However, if such a gap, ie, an air layer, exists, the reflection loss of light due to the difference in refractive index between the protection panel and the air layer and between the air layer and the display module increases, which may deteriorate the image quality of the display.

[0006] Therefore, it is proposed to improve the image quality of the display by filling the gap between the protective panel and the display module with an adhesive layer. For example, Patent Document 1 discloses an adhesive layer having a shear storage modulus (G') of 1.0×10 5 Pa or less and a pressure-sensitive adhesive layer with a gel fraction of 40% or more.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2010-97070 Summary of the invention

[0010] Technical Problems to be Solved by the Invention

[0011] In Patent Document 1, the storage modulus of the adhesive layer at room temperature is set to be relatively low, thereby improving the step tracking property. However, when the storage modulus at room temperature is set to be relatively low as described above, the storage modulus at high temperature will be excessively reduced, which will cause problems under durable conditions. For example, bubbles will be generated near the step when high temperature and high humidity conditions are applied. In addition, in the past, the adhesive layer has the situation of optical unevenness such as appearance deformation observed near the step.

[0012] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an adhesive composition, an adhesive, an adhesive sheet, and a laminate which are excellent in step followability and can suppress the occurrence of optical unevenness.

[0013] Technical means to solve technical problems

[0014] In order to achieve the above-mentioned object, first, the present invention provides an adhesive composition, characterized in that it comprises a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) comprises an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer (Invention 1).

[0015] [Chemical formula 1]

[0016]

[0017] In the above invention (Invention 1), since the above components are contained, the obtained adhesive can exert good cohesive force even without containing a cross-linking agent, and has excellent operability (for example, operability when using an adhesive sheet, etc.). In addition, while exerting the cohesive force, it also exerts excellent stress relaxation properties, and has excellent step tracking properties from the initial stage to high temperature and high humidity. Furthermore, the above excellent stress relaxation properties can suppress the occurrence of optical unevenness (optical deformation, etc.). In addition, since the above adhesive composition does not need to contain a cross-linking agent, when obtaining the adhesive, no curing period (ripening) is required, which can improve the productivity of the adhesive sheet.

[0018] In the above invention (Invention 1), it is preferred that the (meth)acrylate polymer (A) contains 0.5% by mass or more and 40% by mass or less of the ethylene carbonate-containing monomer as a monomer unit constituting the polymer (Invention 2).

[0019] In the above inventions (Inventions 1 and 2), it is preferred that the ionic compound (B) is an alkali metal salt (Invention 3).

[0020] In the above inventions (Inventions 1 to 3), the content of the ionic compound (B) in the adhesive composition is preferably 0.1 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A) (Invention 4).

[0021] In the above inventions (Inventions 1 to 4), it is preferred that the content of the crosslinking agent in the adhesive composition is 0.1 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A) (Invention 5).

[0022] Second, the present invention provides an adhesive (Invention 6) obtained by cross-linking the adhesive composition (Inventions 1 to 5).

[0023] Thirdly, the present invention provides an adhesive sheet comprising at least an adhesive layer, wherein the adhesive layer is composed of the adhesive (Invention 6) (Invention 7).

[0024] Fourthly, the present invention provides an adhesive sheet comprising at least an adhesive layer, characterized in that:

[0025] The pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a strain amount of 50% or more and 260% or less 1210 seconds after a stress of 7950 Pa is applied to the pressure-sensitive adhesive at 25° C.,

[0026] For the adhesive constituting the adhesive layer, the maximum relaxation modulus value measured when the adhesive is subjected to 10% strain in accordance with JIS K7244-1 is defined as the maximum relaxation modulus G(t). max (MPa), from the measurement to the maximum relaxation modulus G(t) max The adhesive was continuously strained by 10% from the beginning until 3757 seconds later, and the minimum relaxation modulus value measured during this period was defined as the minimum relaxation modulus G(t). min (MPa), and the relaxation modulus change value ΔlogG(t) calculated by the following formula (X) is 1.2 or more and 2.0 or less (Invention 8).

[0027] ΔlogG(t)=logG(t) max -logG(t) min …(X)

[0028] In the above inventions (Inventions 7 and 8), it is preferred that the gel fraction of the adhesive constituting the adhesive layer is 0% or more and 60% or less (Invention 9).

[0029] In the above inventions (Inventions 7 to 9), it is preferred that the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a storage modulus (G′) at 50° C. of 0.01 MPa to 1 MPa (Invention 10).

[0030] In the above inventions (Inventions 7 to 10), it is preferred that the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a storage modulus (G′) of 0.01 MPa to 1 MPa at 25° C. (Invention 11).

[0031] In the above inventions (Inventions 7 to 11), it is preferred that the adhesive layer has an adhesive strength to soda-lime glass of 1 N / 25 mm or more and 100 N / 25 mm or less (Invention 12).

[0032] In the above inventions (Inventions 7 to 12), preferably, the adhesive sheet includes two release sheets, and the adhesive layer is sandwiched by the release sheets so as to be in contact with release surfaces of the two release sheets (Invention 13).

[0033] Fifth, the present invention provides a laminate comprising a display body constituent component, another display body constituent component, and an adhesive layer for bonding the one display body constituent component and the other display body constituent component to each other, characterized in that the adhesive layer is formed by the adhesive layer of the adhesive sheet (Inventions 7 to 13) (Invention 14).

[0034] In the above invention (Invention 14), it is preferred that at least one of the one display constituting member and the other display constituting member has a step on a surface on a side to be bonded by the adhesive layer (Invention 15).

[0035] Effects of the Invention

[0036] The adhesive composition, adhesive, adhesive sheet and laminate of the present invention are excellent in step followability and can suppress the occurrence of optical unevenness. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a cross-sectional view of an adhesive sheet according to one embodiment of the present invention.

[0038] Figure 2 This is a cross-sectional view of a laminated body according to one embodiment of the present invention. DETAILED DESCRIPTION

[0039] Hereinafter, embodiments of the present invention will be described.

[0040] [Adhesive composition]

[0041] The adhesive composition of one embodiment of the present invention (hereinafter sometimes referred to as "adhesive composition P") preferably contains a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) contains an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer.

[0042] [Chemical formula 1]

[0043]

[0044] In this specification, (meth)acrylic acid refers to both acrylic acid and methacrylic acid. Other similar terms are the same. In addition, "polymer" also includes the concept of "copolymer".

[0045] Since (meth) acrylate polymer (A) is composed of the above-mentioned ethylene carbonate-containing monomer, the adhesive composition P of the present embodiment includes ethylene carbonate structure as the side chain of (meth) acrylate polymer (A). If (meth) acrylate polymer (A) includes ethylene carbonate structure in the side chain, the interaction between the side chains becomes stronger, and the glass transition temperature (Tg) of (meth) acrylate polymer (A) becomes relatively high. Thus, the cohesive force of the obtained adhesive becomes stronger. In addition, the ethylene carbonate structure includes two carbonyl dipoles. Thus, the ethylene carbonate structure as the side chain of (meth) acrylate polymer (A) is bonded with the ionic compound (B) by interaction to form a quasi-crosslinked structure. By containing the crosslinked structure, the obtained adhesive will also exert good cohesive force even if it does not contain a crosslinking agent, and the operability (for example, the workability when using an adhesive sheet, etc.) is excellent. Further, from the perspective of the polarity of the ethylene carbonate structure, the adhesive force of the obtained adhesive, especially the adhesive force to glass is high. On the other hand, when a predetermined pressure (and heat) is applied to the adhesive, the above-mentioned cross-linked structure relaxes and exhibits excellent stress relaxation properties. For example, when the adhered object of the adhesive has a step, it is easy to follow the shape of the step. Afterwards, even if the predetermined pressure (and heat) is removed, the state of following the shape of the step can be maintained well, and a pseudo-cross-linked structure is formed again. In this case, since the stress in the adhesive when following the shape of the step is not easy to remain, the force of the adhesive to restore to the state before following can be suppressed to a smaller level, and the state of following the shape of the step can be maintained well. Through these effects, the adhesive sheet obtained using the adhesive has excellent step following properties in the initial stage ~ under high temperature and high humidity. In addition, the so-called "initial stage" here does not include the situation just after the attachment is completed. In addition, the residual stress of a general adhesive appears significantly near the step difference, etc. For example, even in the case of excellent step tracking performance at the initial stage to high temperature and high humidity (i.e., no bubbles, floating, or peeling are generated near the step difference, etc.), sometimes optical unevenness (optical deformation, etc.) may occur near the step difference, etc. due to deformation of the adhesive caused by the force of the adhesive to restore to the state before following. However, the adhesive sheet obtained using the adhesive obtained from the adhesive composition P of this embodiment can suppress the force of the adhesive to restore to the state before following, so that the suppression of optical unevenness near the step difference, etc. is excellent, for example, the image quality and appearance of the display can be excellent. Furthermore, since the adhesive composition of this embodiment does not need to contain a cross-linking agent, no curing period (ripening) is required when the adhesive is obtained, so the productivity of the adhesive sheet can be improved. In addition, in addition to general cross-linking based on covalent bonds, the "cross-linking" in this specification also includes pseudo-cross-linking based on mutual interaction (including coordination bonds, ionic bonds, intermolecular forces, etc., but not limited thereto).

[0046] (1) Components of the adhesive composition

[0047] (1-1) (Meth)acrylate polymer (A)

[0048] The ethylene carbonate-containing monomer having the ethylene carbonate structure represented by the above formula (1) is not particularly limited as long as it contains the ethylene carbonate structure and can undergo polymerization reaction with other monomers constituting the (meth)acrylate polymer (A).

[0049] Preferred examples of ethylene carbonate-containing monomers include (meth)acrylates having a structure in which an organic group having an ethylene carbonate structure is bonded to a (meth)acryloyloxy group. Examples of such (meth)acrylates include acrylates represented by the following formula (2) or methacrylates represented by the following formula (3).

[0050] [Chemical formula 2]

[0051]

[0052] [Chemical formula 3]

[0053]

[0054] In addition, in formula (2) and formula (3), n represents an integer greater than 0. In the (meth) acrylate represented by the above formula (2) and formula (3), preferably n is a (meth) acrylate greater than 1, and preferably n is a (meth) acrylate greater than 2. By making n greater than 1, the ethylene carbonate group as the side chain of the (meth) acrylate polymer (A) is present in a position relatively far from the main chain, so that the probability of the ethylene carbonate structures present in the obtained adhesive overlapping each other is increased. Thus, the stacking effect between the ethylene carbonate structures is effective, and it is easy to appropriately exert the mechanical properties (strain, relaxation modulus variation value, storage modulus) and adhesion described later. In addition, the ethylene carbonate structure is prone to interact with the ionic compound (B), and it is easier to form a pseudo-crosslinked structure, and the cohesive force increases. Through these effects, the step tracking property of the obtained adhesive becomes more excellent. In addition, the inhibition of optical unevenness is excellent, and the operability is also excellent at the same time. The upper limit of n is not particularly limited. From the perspective of polymerizability, it is preferably 10 or less, more preferably 6 or less, particularly preferably 4 or less, and further preferably 3 or less. Among them, from the perspective of easily improving the mechanical properties (strain, relaxation modulus change value, storage modulus) and adhesion of the obtained adhesive, and better step tracking, (meth)acrylates with n=2 are preferred, and methacrylate (2-oxo-1,3-dioxolane-4-yl) methyl ester with n=2 in formula (3) is particularly preferred. In addition, the ethylene carbonate-containing monomer can be used alone or in combination of two or more.

[0055] (Meth) acrylate polymer (A) preferably contains more than 0.5 mass %, more preferably contains more than 1 mass %, particularly preferably contains more than 5 mass %, and further preferably contains more than 10 mass % of the above-mentioned ethylene carbonate-containing monomer as the monomer unit constituting the polymer. Thus, the stacking effect between the ethylene carbonate structures exerts an effect, and it is easy to appropriately exert the mechanical properties (strain, relaxation modulus variation value, storage modulus) and adhesion described later. In addition, it is easy to interact with each other between the ethylene carbonate structure and the ionic compound (B), and it is easier to form a quasi-crosslinked structure, and cohesion increases. By the above-mentioned effect, the step difference tracking property of the obtained adhesive is more excellent. And the inhibition of optical unevenness is excellent, and the operability is also excellent at the same time. Further, from the perspective of polarity, the adhesion of the adhesive, especially the adhesion to glass becomes high.

[0056] On the other hand, the (meth)acrylate polymer (A) preferably contains 40% by mass or less, more preferably 30% by mass or less, particularly preferably 25% by mass or less, and further preferably 20% by mass or less of the above-mentioned ethylene carbonate-containing monomer as a monomer unit constituting the polymer. Thus, it is easy to satisfy the mechanical properties (strain, relaxation modulus variation value, storage modulus) described later, and the step followability is more excellent.

[0057] The (meth)acrylate polymer (A) in this embodiment preferably contains an alkyl (meth)acrylate as a monomer unit constituting the polymer. Thus, the obtained adhesive can exhibit good adhesiveness. The alkyl group may be linear or branched.

[0058] As the alkyl (meth)acrylate, from the viewpoint of adhesiveness, an alkyl (meth)acrylate having an alkyl group with 1 to 20 carbon atoms is preferred. Examples of the alkyl (meth)acrylate having an alkyl group with 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearic (meth)acrylate, and the like.

[0059] Among the above, from the viewpoint of imparting good adhesiveness, alkyl (meth)acrylates having an alkyl group with 2 to 12 carbon atoms are more preferred, and alkyl (meth)acrylates having an alkyl group with 4 to 10 carbon atoms are particularly preferred. Specifically, n-butyl (meth)acrylate is preferred, and n-butyl acrylate is particularly preferred. These may be used alone or in combination of two or more.

[0060] From the perspective of imparting good adhesion, the (meth)acrylate polymer (A) preferably contains 50% by mass or more, more preferably 60% by mass or more, particularly preferably 70% by mass or more, and further preferably 80% by mass or more of the (meth)acrylate alkyl ester as a monomer unit constituting the polymer. In addition, from the perspective of ensuring the content of other monomers (especially ethylene carbonate-containing monomers), it is preferred that the (meth)acrylate alkyl ester be contained in an amount of 99.6% by mass or less, more preferably 99% by mass or less, particularly preferably 95% by mass or less, and further preferably 90% by mass or less.

[0061] The (meth)acrylate polymer (A) also preferably contains a reactive functional group-containing monomer having a reactive functional group in the molecule as a monomer constituting the polymer. By containing a reactive functional group-containing monomer, it is easier to exert the interaction between the (meth)acrylate polymer (A) and the ionic compound (B), and it is easier to form a pseudo-crosslinked structure. As a result, the cohesive force of the resulting adhesive is improved, and it is easy to meet the mechanical properties (strain, relaxation modulus change value, storage modulus) described later, and the step tracking property is more excellent.

[0062] As the above-mentioned reactive functional group-containing monomer, preferably, there can be listed a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), etc. Among them, from the perspective of easily forming the above-mentioned pseudo-crosslinked structure, a hydroxyl group-containing monomer is preferred. These reactive functional group-containing monomers can be used alone or in combination of two or more.

[0063] Examples of hydroxyl-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among them, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred from the perspective of easily forming the aforementioned pseudo-crosslinked structure, and 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate are particularly preferred. These hydroxyl-containing monomers may be used alone or in combination of two or more.

[0064] Examples of the carboxyl group-containing monomer include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. These carboxyl group-containing monomers may be used alone or in combination of two or more.

[0065] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, etc. These amino group-containing monomers may be used alone or in combination of two or more.

[0066] According to the following limit, (meth) acrylate polymer (A) preferably contains more than 0.1% by mass, more preferably contains more than 0.5% by mass, and particularly preferably contains more than 1% by mass of reactive functional group-containing monomers as monomers constituting the polymer. In addition, according to the upper limit, (meth) acrylate polymer (A) preferably contains less than 10% by mass, more preferably contains less than 8% by mass, particularly preferably contains less than 6% by mass, and further preferably contains less than 3% by mass of reactive functional group-containing monomers as monomer units constituting the polymer. (Meth) acrylate polymer (A) is easier to form the above-mentioned pseudo-crosslinked structure by containing reactive functional group-containing monomers as monomer units constituting the polymer in the above range. Thus, the cohesive force of the resulting adhesive is improved, and it is easy to meet the mechanical properties (strain, relaxation modulus variation value, storage modulus) described later, and the step tracking property is more excellent. In addition, the inhibition of optical unevenness is excellent, and the operability is also excellent at the same time.

[0067] The (meth)acrylate polymer (A) in this embodiment may further contain other monomers as monomers constituting the polymer. As other monomers, for example, (meth)acrylates containing alicyclic structures such as dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate; (meth)acrylate alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; non-crosslinked acrylamides such as acrylamide and methacrylamide; non-crosslinked (meth)acrylates having tertiary amino groups such as N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate; vinyl acetate; styrene, etc. These other monomers may be used alone or in combination of two or more.

[0068] The polymerization form of the (meth)acrylate polymer (A) in this embodiment may be a random polymer or a block polymer. In addition, the (meth)acrylate polymer (A) can be obtained by polymerizing the above-mentioned monomers in a conventional manner. For example, it can be prepared by polymerization by emulsion polymerization, solution polymerization, suspension polymerization, bulk polymerization, aqueous solution polymerization, etc. Among them, from the perspective of stability during polymerization and ease of operation during use, it is preferably prepared by solution polymerization in an organic solvent.

[0069] The weight average molecular weight of (meth) acrylate polymer (A) is preferably more than 100,000, more preferably more than 300,000, particularly preferably more than 500,000, and more preferably more than 650,000. In addition, the weight average molecular weight is preferably less than 2,000,000, more preferably less than 1,500,000, particularly preferably less than 1,000,000, and more preferably less than 800,000. By making the weight average molecular weight of (meth) acrylate polymer (A) be the above range, the obtained adhesive easily satisfies the mechanical properties (strain, relaxation modulus variation, storage modulus) described later, and the step tracking property is more excellent. In addition, the inhibition of optical unevenness is excellent, and the operability is also excellent at the same time. In addition, the weight average molecular weight in this specification is the standard polystyrene conversion value measured by gel permeation chromatography (GPC) method.

[0070] In addition, the adhesive composition P of the present embodiment may contain one of the above-mentioned (meth)acrylate polymers (A), or may contain two or more of the above-mentioned (meth)acrylate polymers (A). In addition, the adhesive composition P of the present embodiment may contain other (meth)acrylate polymers while containing the above-mentioned (meth)acrylate polymer (A).

[0071] (1-2) Ionic compounds (B)

[0072] The ionic compound in this specification refers to a compound in which a cation and an anion are bonded mainly by electrostatic attraction. The ionic compound (B) in this embodiment may be a liquid (ionic liquid) or a solid (ionic solid) at room temperature.

[0073] Examples of the ionic compound (B) include alkali metal salts, alkaline earth metal salts, nitrogen-containing onium salts, sulfur-containing onium salts, phosphorus-containing onium salts, etc. Among them, alkali metal salts or alkaline earth metal salts are preferred, and alkali metal salts are particularly preferred, from the perspective of easily forming the above-mentioned pseudo-crosslinked structure with the (meth)acrylate polymer (A). In addition, the ionic compound (B) can be used alone or in combination of two or more.

[0074] Specific examples of alkali metal salts include potassium bis(fluorosulfonyl)imide, lithium bis(fluorosulfonyl)imide, potassium bis(fluoromethylsulfonyl)imide, lithium bis(fluoromethylsulfonyl)imide, potassium bis(trifluoromethylsulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide. Among them, lithium bis(trifluoromethylsulfonyl)imide is preferred from the viewpoint of easy formation of the above-mentioned pseudo-crosslinked structure.

[0075] Relative to 100 parts by mass of (meth) acrylate polymer (A), the content of the ionic compound (B) in the adhesive composition is preferably more than 0.1 parts by mass, more preferably more than 0.2 parts by mass, particularly preferably more than 0.3 parts by mass, and more preferably more than 0.4 parts by mass. In addition, relative to 100 parts by mass of (meth) acrylate polymer (A), the content of the ionic compound (B) is preferably less than 2 parts by mass, more preferably less than 1.5 parts by mass, particularly preferably less than 1 part by mass, and more preferably less than 0.7 parts by mass. By making the content of the ionic compound (B) within the above range, the degree of the above-mentioned proposed cross-linking becomes appropriate. Therefore, the obtained adhesive easily satisfies the mechanical properties (strain, relaxation modulus variation, storage modulus) described later, and the step tracking is more excellent. In addition, the inhibition of optical unevenness is excellent, and the operability is also excellent at the same time.

[0076] (1-3) Various additives

[0077] Various additives commonly used in acrylic adhesives, such as crosslinking agents, silane coupling agents, rust inhibitors, ultraviolet absorbers, tackifiers, antioxidants, light stabilizers, softeners, refractive index adjusters, etc., can be added to the adhesive composition P as needed. In addition, the polymerization solvent and dilution solvent described later are not included in the additives constituting the adhesive composition P.

[0078] As described above, since the adhesive composition P forms a pseudo-crosslinked structure, a crosslinking agent is not required. Therefore, aging is not required when obtaining the adhesive. From this perspective, the adhesive composition P preferably does not contain a crosslinking agent.

[0079] However, the adhesive composition P does not exclude the case where it contains a crosslinking agent. When the adhesive composition P contains a crosslinking agent, the content of the crosslinking agent is preferably 0.1 parts by mass or less, more preferably 0.04 parts by mass or less, and particularly preferably 0.01 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A). In addition, as the crosslinking agent here, there can be listed crosslinking agents that form a covalent bond with the (meth)acrylate polymer (A), such as isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, etc.

[0080] (2) Preparation of adhesive composition

[0081] The adhesive composition P can be prepared by preparing a (meth)acrylate polymer (A), mixing the obtained (meth)acrylate polymer (A) and the ionic compound (B), and simultaneously adding additives and the like as needed.

[0082] The (meth)acrylate polymer (A) can be prepared by polymerizing a mixture of monomers constituting the polymer by a conventional free radical polymerization method. The polymerization of the (meth)acrylate polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as required. However, the present invention is not limited thereto, and polymerization can also be carried out under solvent-free conditions. As polymerization solvents, for example, ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, etc. can be listed, and two or more thereof can be used simultaneously.

[0083] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more thereof may be used simultaneously. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].

[0084] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di-2-ethoxyethyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0085] Furthermore, by adding a chain transfer agent such as 2-mercaptoethanol in the above-mentioned polymerization step, the weight average molecular weight of the obtained polymer can be adjusted.

[0086] After obtaining the (meth)acrylate polymer (A), the ionic compound (B) and the required diluting solvent and additives are added to the solution of the (meth)acrylate polymer (A) and mixed thoroughly to obtain a solvent-diluted adhesive composition P (coating solution). In addition, for any of the above-mentioned components, when a solid substance is used, or when precipitation occurs when mixed with other components in an undiluted state, the component can be dissolved or diluted in a diluting solvent alone before mixing with other components.

[0087] As the above-mentioned dilution solvent, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane and dichloroethane; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; cellosolve-type solvents such as ethyl cellosolve, etc. can be used.

[0088] The concentration and viscosity of the coating solution prepared in this way are not particularly limited as long as they are within the range that can be coated, and can be appropriately selected according to the situation. For example, the adhesive composition P is diluted in a manner such that the concentration is 10 to 60% by mass. In addition, when obtaining the coating solution, the addition of a diluting solvent or the like is not a necessary condition, and as long as the adhesive composition P is a viscosity that can be coated, a diluting solvent may not be added. At this time, the adhesive composition P is a coating solution in which the polymerization solvent of the (meth)acrylate polymer (A) is directly used as the diluting solvent.

[0089] [Adhesive]

[0090] The adhesive according to one embodiment of the present invention is obtained from the adhesive composition P according to the above embodiment, and specifically, is obtained by crosslinking (pseudo-crosslinking) the adhesive composition P.

[0091] The crosslinking of the adhesive composition P can generally be performed by heat treatment. In addition, the drying treatment when volatilizing the dilution solvent and the like from the coating film of the adhesive composition P applied to the desired object can also be used as the heating treatment.

[0092] The heating temperature of the heat treatment is preferably 50 to 150° C., particularly preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, particularly preferably 50 seconds to 5 minutes.

[0093] When the adhesive composition P contains a crosslinking agent, a curing period is preferably provided after the above-mentioned heat treatment in order to complete the crosslinking reaction, but the adhesive composition P of this embodiment does not need to contain a crosslinking agent, and a curing period is not required in this case. Thus, the productivity of the adhesive sheet can be improved.

[0094] [Adhesive sheet]

[0095] The adhesive sheet according to one embodiment of the present invention includes at least an adhesive layer, and is preferably an adhesive sheet in which a release sheet is laminated on one or both surfaces of the adhesive layer.

[0096] The adhesive sheet of this embodiment is preferably used to bond one component to another component, and is particularly preferably used in the case where at least one of the components has a step difference on the surface of at least the adhesive layer side. As the above-mentioned component, a display body component can be preferably listed, and therefore, the adhesive sheet of this embodiment is preferably used for optical purposes, but is not limited thereto.

[0097] The adhesive layer of the adhesive sheet according to one embodiment of the present invention is composed of the above-mentioned adhesive. The adhesive layer or the adhesive constituting the adhesive layer preferably has the physical properties described below.

[0098] In the adhesive sheet of another embodiment of the present invention, for the adhesive constituting the above-mentioned adhesive layer, the strain amount 1210 seconds after the stress of 7950 Pa is applied to the adhesive at 25° C. is 50% or more and 260% or less, and for the adhesive constituting the above-mentioned adhesive layer, the maximum relaxation modulus value measured when the adhesive is subjected to 10% strain in accordance with JIS K7244-1 is set as the maximum relaxation modulus G(t) max (MPa), from the measurement to the maximum relaxation modulus G(t) max The adhesive was continuously strained by 10% from the beginning until 3757 seconds later, and the minimum relaxation modulus value measured during this period was defined as the minimum relaxation modulus G(t). min (MPa), and the relaxation modulus change value ΔlogG(t) calculated by the following formula (X) is preferably 1.2 or more and 2.0 or less.

[0099] ΔlogG(t)=logG(t) max -logG(t) min …(X)

[0100] The details of the method for measuring the strain amount (%) and the method for measuring the relaxation modulus G(t) are as described in the test examples below. In addition, "when a stress of 7950 Pa is applied to the adhesive" means the time point when the stress reaches 7950 Pa when the stress is applied to the adhesive.

[0101] By making the adhesive constituting the adhesive layer of the adhesive sheet of this embodiment have the above-mentioned physical properties, the adhesive layer is easily deformed and exhibits excellent stress relaxation properties, so it has excellent step tracking properties from the initial stage to high temperature and high humidity. In addition, it has excellent suppression of optical unevenness and excellent handleability.

[0102] In particular, if the strain amount is 50% or more, when an external force is applied to the adhesive layer, a moderate strain will be generated and the adhesive layer will be easily deformed, so that the step tracking property is excellent in the initial stage and after autoclave treatment. In addition, if the strain amount is 50% or more, the stress relaxation modulus change value ΔlogG(t) tends to increase and is easy to meet the desired range. From the above perspective, the strain amount is more preferably 100% or more, particularly preferably 150% or more, and further preferably 180% or more.

[0103] In addition, if the strain is 260% or less, the adhesive shows high cohesion, and even under high temperature and high humidity conditions, the step tracking is excellent. In addition, the adhesive is not prone to cohesive failure, and it is possible to suppress the occurrence of residual adhesive when the adhesive sheet is peeled off from the adherend. Further, the obtained adhesive sheet has excellent operability. From the above perspective, the strain is more preferably 240% or less, particularly preferably 225% or less, and further preferably 200% or less.

[0104] On the other hand, if the above-mentioned relaxation modulus change value ΔlogG (t) is 1.2 or more, the stress relaxation is excellent. Therefore, after the adhesive sheet is attached to the step difference of the adherend, it is easy to promote the stress relaxation inside the adhesive, especially to relax the residual stress near the step difference. Therefore, even under high temperature and high humidity conditions, the floating and peeling caused by the residual stress during the step difference attachment will be suppressed, and the excellent step difference tracking property will be exerted. From the above perspective, the above-mentioned relaxation modulus change value ΔlogG (t) is more preferably 1.3 or more, particularly preferably 1.4 or more, and more preferably 1.44 or more.

[0105] In addition, if the relaxation modulus variation value ΔlogG(t) is 2.0 or less, the adhesive can easily exhibit appropriate stress relaxation properties. From the above perspective, the relaxation modulus variation value ΔlogG(t) is more preferably 1.8 or less, particularly preferably 1.6 or less, and further preferably 1.5 or less.

[0106] The lower limit of the gel fraction of the adhesive constituting the above-mentioned adhesive layer is preferably 0% or more, more preferably 0.4% or more, particularly preferably 0.8% or more, and further preferably 1.2% or more. In addition, the upper limit of the above-mentioned gel fraction is preferably 60% or less, more preferably 40% or less, particularly preferably 20% or less, further preferably 10% or less, and most preferably 3% or less. By making the gel fraction of the adhesive constituting the above-mentioned adhesive layer within the above-mentioned range, it is easy to adjust the above-mentioned strain amount and relaxation modulus change value ΔlogG(t) to the above-mentioned range. In addition, by making the gel fraction below 3%, the adhesive can be quasi-crosslinked, and the initial step tracking property is more excellent. In addition, the method for determining the gel fraction of the adhesive is as shown in the test example described later.

[0107] The lower limit of the storage modulus (G') of the adhesive constituting the above-mentioned adhesive layer at 25°C is preferably 0.01MPa or more, more preferably 0.05MPa or more, particularly preferably 0.08MPa or more, and further preferably 0.1MPa or more. By setting the lower limit of the storage modulus (G') at 25°C to the above-mentioned range, the above-mentioned strain amount and relaxation modulus change value ΔlogG(t) of the obtained adhesive are easy to satisfy the above-mentioned range, and the step tracking property under high temperature and high humidity conditions is more excellent. In addition, it is easy to satisfy the adhesive force described later. In addition, the test method of the storage modulus (G') is shown in the test example described later.

[0108] On the other hand, the upper limit of the storage modulus (G') of the adhesive constituting the above-mentioned adhesive layer at 25°C is preferably 1 MPa or less, more preferably 0.8 MPa or less, particularly preferably 0.5 MPa or less, and further preferably 0.2 MPa or less. By setting the upper limit of the storage modulus (G') at 25°C to the above-mentioned range, the above-mentioned strain amount and relaxation modulus change value ΔlogG(t) of the obtained adhesive are easy to satisfy the above-mentioned range, and the initial step tracking property is more excellent. In addition, it is easy to satisfy the adhesive force described later.

[0109] The lower limit of the storage modulus (G') of the adhesive constituting the above-mentioned adhesive layer at 50°C is preferably 0.01MPa or more, more preferably 0.02MPa or more, particularly preferably 0.03MPa or more, and further preferably 0.04MPa or more. By setting the lower limit of the storage modulus (G') at 50°C to the above-mentioned range, the above-mentioned strain amount and relaxation modulus change value ΔlogG(t) of the obtained adhesive are easy to satisfy the above-mentioned range, and the step tracking property under high temperature and high humidity conditions is more excellent. In addition, it is easy to satisfy the adhesive force described later.

[0110] On the other hand, the upper limit of the storage modulus (G') of the adhesive constituting the above-mentioned adhesive layer at 50°C is preferably 1MPa or less, more preferably 0.5MPa or less, particularly preferably 0.3MPa or less, and further preferably 0.1MPa or less. By setting the upper limit of the storage modulus (G') at 50°C to the above range, the strain amount and relaxation modulus change value ΔlogG(t) of the obtained adhesive easily satisfy the above range, and the initial step tracking property, especially the step tracking property after lamination using an autoclave or the like, is more excellent. In addition, it is easy to satisfy the adhesive force described later.

[0111] The lower limit of the storage modulus (G') of the adhesive constituting the above-mentioned adhesive layer at 85°C is preferably 0.01MPa or more, particularly preferably 0.015MPa or more, and further preferably 0.02MPa or more. By setting the lower limit of the storage modulus (G') at 85°C to the above-mentioned range, the above-mentioned strain amount and relaxation modulus change value ΔlogG(t) of the obtained adhesive are easy to satisfy the above-mentioned range, and the step tracking property under high temperature and high humidity conditions is more excellent. In addition, it is easy to satisfy the adhesive force described later.

[0112] On the other hand, the upper limit of the storage modulus (G') of the adhesive constituting the above-mentioned adhesive layer at 85°C is preferably 1MPa or less, more preferably 0.5MPa or less, particularly preferably 0.1MPa or less, and most preferably 0.03MPa or less. By setting the upper limit of the storage modulus (G') at 85°C to the above range, the strain amount and relaxation modulus change value ΔlogG(t) of the obtained adhesive easily satisfy the above range, and the step tracking property under high temperature and high humidity conditions is more excellent. In addition, it is easy to satisfy the adhesive force described later.

[0113] The lower limit of the adhesion of the adhesive sheet of the present embodiment to the soda-lime glass is preferably greater than 1N / 25mm, more preferably 5N / 25mm or more, particularly preferably 10N / 25mm or more, and further preferably 20N / 25mm or more. If the lower limit of the adhesion is within the above range, the step tracking property under high temperature and high humidity conditions is more excellent. On the other hand, although the upper limit of the adhesion to the soda-lime glass is not particularly limited, it is preferably 100N / 25mm or less, more preferably 60N / 25mm or less, particularly preferably 40N / 25mm or less, and further preferably 30N / 25mm or less, considering that reworkability may sometimes be required.

[0114] The lower limit of the adhesion of the adhesive sheet 1 of the present embodiment to the alkali-free glass is preferably greater than 1N / 25mm, more preferably 5N / 25mm or more, particularly preferably 10N / 25mm or more, and further preferably 20N / 25mm or more. If the lower limit of the adhesion is within the above range, the step tracking property under high temperature and high humidity conditions is more excellent. On the other hand, although the upper limit of the adhesion to the alkali-free glass is not particularly limited, considering the need for heavy workability, it is preferably 100N / 25mm or less, more preferably 60N / 25mm or less, particularly preferably 40N / 25mm or less, and further preferably 30N / 25mm or less.

[0115] The above-mentioned adhesive strength is basically the adhesive strength measured by the 180-degree peeling method in accordance with JIS Z0237:2009, and the specific test method is shown in the test examples described later.

[0116] The adhesive or adhesive layer having the above-mentioned physical properties can be preferably obtained using the above-mentioned adhesive composition P, but is not limited thereto.

[0117] Here, a specific structure of an example of the adhesive sheet of this embodiment is shown. Figure 1 .like Figure 1 As shown, an adhesive sheet 1 of one embodiment is composed of two release sheets 12a, 12b and an active energy ray-curable adhesive layer 11, and the adhesive layer 11 is sandwiched by the two release sheets 12a, 12b in a manner of contacting the release surfaces of the two release sheets 12a, 12b. In addition, the release surface of the release sheet in this specification refers to a surface of the release sheet that has release properties, including any one of a surface that has been subjected to a release treatment and a surface that shows release properties even if a release treatment is not applied.

[0118] 1. Each component

[0119] 1-1. Adhesive layer

[0120] The adhesive layer 11 of the adhesive sheet 1 of the present embodiment has the above-mentioned composition and physical properties.

[0121] The thickness of the adhesive layer 11 in the present embodiment (the value measured based on JIS K7130) is preferably 1 μm or more, more preferably 5 μm or more, particularly preferably 10 μm or more, and further preferably 20 μm or more. Thus, it is easy to exert the above-mentioned adhesion, and the step tracking property is more excellent. In addition, the thickness of the adhesive layer 11 is preferably 100 μm or less, more preferably 75 μm or less, particularly preferably 50 μm or less, and further preferably 30 μm or less. Thus, the poor appearance of the indentation, scratching, etc. of the adhesive layer 11 can be suppressed. In addition, the thinning of the laminate (display body, etc.) obtained using the adhesive sheet 1 becomes possible. In addition, the adhesive layer 11 can be formed as a single layer, and it can also be formed by stacking multiple layers.

[0122] 1-2. Peel off sheet

[0123] The release sheets 12a and 12b protect the adhesive layer 11 until the adhesive sheet 1 is used, and are peeled off when the adhesive sheet 1 (adhesive layer 11) is used. The adhesive sheet 1 of the present embodiment does not necessarily need one or both of the release sheets 12a and 12b.

[0124] As the release sheets 12a and 12b, for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene vinyl acetate film, ionomer resin film, ethylene-(meth)acrylic acid polymer film, ethylene-(meth)acrylic acid ester polymer film, polystyrene film, polycarbonate film, polyimide film, fluororesin film, etc. can be used. In addition, cross-linked films of these films can also be used. And, laminated films of these films can also be used.

[0125] It is preferred that the release surfaces of the release sheets 12a and 12b be subjected to a release treatment. Examples of the release agent used in the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents.

[0126] The thickness of the release sheets 12a and 12b is not particularly limited, but is generally about 20 to 150 μm.

[0127] 2. Manufacturing of adhesive sheet

[0128] As a manufacturing example of the adhesive sheet 1, the coating solution of the above-mentioned adhesive composition P is applied to the release surface of a release sheet 12a (or 12b) and heat-treated, and after the adhesive composition P is cross-linked to form an adhesive layer 11, the release surface of another release sheet 12b (or 12a) is superimposed on the adhesive layer 11. The above-mentioned adhesive sheet 1 is obtained. The conditions for the heat treatment are as described above. By using the adhesive composition P in the formation of the adhesive layer 11, the adhesive sheet 1 can be manufactured without aging.

[0129] As another manufacturing example of the adhesive sheet 1, the coating solution of the adhesive composition P is applied to the release surface of a release sheet 12a and heat-treated, so that the adhesive composition P is cross-linked to form an adhesive layer, and a release sheet 12a with an adhesive layer is obtained. In addition, the coating solution of the adhesive composition P is applied to the release surface of another release sheet 12b and heat-treated, so that the adhesive composition P is cross-linked to form an adhesive layer, and a release sheet 12b with an adhesive layer is obtained. Then, the release sheet 12a with an adhesive layer and the release sheet 12b with an adhesive layer are laminated in a manner that the two adhesive layers are in contact with each other, as an adhesive layer 11. The above-mentioned adhesive sheet 1 is thus obtained. According to this manufacturing example, even when the adhesive layer 11 is thick, it can be stably manufactured.

[0130] As a method for applying the coating solution of the adhesive composition P, for example, a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, a gravure coating method, etc. can be utilized.

[0131] [Laminated body]

[0132] A laminated body according to one embodiment of the present invention comprises a display component, another display component, and an adhesive layer for bonding the display components to each other, wherein the adhesive layer is formed by the adhesive layer of the adhesive sheet. The laminated body is a display (display panel) or a component thereof.

[0133] Preferably, at least one of the above-mentioned one display body constituent member and the other display body constituent member has a step difference on the surface of the side to which the above-mentioned adhesive layer is attached, and the step difference is preferably a step difference caused by the printing layer. Since the above-mentioned adhesive layer has excellent step difference tracking properties under high temperature and high humidity conditions in the initial stage, even when the above-mentioned laminate is placed under high temperature and high humidity conditions (for example, 85°C, 85%RH, 96 hours), the generation of bubbles, floating, peeling, etc. near the step difference can be suppressed. In addition, since the above-mentioned adhesive layer is also excellent in suppressing optical unevenness, the occurrence of optical unevenness near the step difference can also be suppressed.

[0134] The specific structure of an example of the laminated body of this embodiment is shown in Figure 2 .

[0135] like Figure 2 As shown, the laminated body 2 of this embodiment is composed of a first display body constituent member 21, a second display body constituent member 22, and an adhesive layer 11, and the adhesive layer 11 is located between the first display body constituent member 21 and the second display body constituent member 22, and is sandwiched by the first display body constituent member 21 and the second display body constituent member 22. In addition, in the laminated body 2 of this embodiment, the first display body constituent member 21 has a step difference on the surface of the adhesive layer 11 side, specifically, the step difference caused by the presence or absence of the printed layer 3.

[0136] The laminate 2 may be a component constituting a part of a display such as a liquid crystal (LCD) display, a light emitting diode (LED) display, an organic electroluminescent (organic EL) display, or an electronic paper, or may be the display itself. In addition, the display may be a touch panel or a flexible display that can be bent repeatedly.

[0137] The adhesive layer 11 of the laminate 2 is formed of the adhesive layer 11 of the adhesive sheet 1 , and is preferably the adhesive layer 11 itself.

[0138] The first display body constituent member 21 and the second display body constituent member 22 are not particularly limited as long as they can adhere to the adhesive layer 11. The first display body constituent member 21 and the second display body constituent member 22 may be made of the same material or different materials.

[0139] The first display component 21 is preferably a protective panel composed of a laminate including a glass plate, a plastic plate, etc. In this case, the printed layer 3 is usually formed in a frame shape on the adhesive layer 11 side of the first display component 21 .

[0140] The glass plate is not particularly limited, and examples thereof include chemically strengthened glass, alkali-free glass, quartz glass, soda-lime glass, barium-strontium-containing glass, aluminosilicate glass, lead glass, borosilicate glass, barium borosilicate glass, etc. The thickness of the glass plate is not particularly limited, and is usually 0.1 to 5 mm, preferably 0.2 to 2 mm.

[0141] The plastic plate is not particularly limited, and examples thereof include acrylic plates, polycarbonate plates, etc. The thickness of the plastic plate is not particularly limited, but is usually 0.2 to 5 mm, preferably 0.4 to 3 mm, particularly preferably 0.6 to 2.5 mm, and further preferably 0.8 to 2.1 mm.

[0142] In addition, various functional layers (transparent conductive film, metal layer, silicon dioxide layer, hard coating layer, anti-glare layer, etc.) may be provided on one or both sides of the glass plate or plastic plate, and optical components may be laminated on one or both sides of the glass plate or plastic plate. In addition, the transparent conductive film and the metal layer may also be patterned.

[0143] The second display component 22 is preferably an optical component to be attached to the first display component 21, a display module (for example, a liquid crystal (LCD) module, a light emitting diode (LED) module, an organic electroluminescent (organic EL) module, etc.), an optical component that is part of the display module, or a stacked body including a display module.

[0144] As the above optical member, for example, anti-scattering film, polarizing plate (polarizing film), polarizer, phase difference plate (phase difference film), viewing angle compensation film, brightness enhancement film, contrast enhancement film, liquid crystal polymer film, diffusion film, semi-transmissive reflection film, transparent conductive film, etc. can be listed. As the anti-scattering film, a hard coating film formed by forming a hard coating layer on one side of a substrate film can be exemplified.

[0145] The material constituting the printed layer 3 is not particularly limited, and a known material used for printing can be used.

[0146] The thickness of the printed layer 3, i.e., the lower limit of the height of the step is preferably 3 μm or more, more preferably 5 μm or more, particularly preferably 7 μm or more, and most preferably 10 μm or more. By setting the lower limit to the above range, it is possible to fully ensure that the shielding of the electrical wiring, etc., cannot be seen from the observer's side. In addition, the upper limit is preferably thinner than the thickness of the adhesive layer, preferably 80 μm or less, more preferably 50 μm or less, particularly preferably 25 μm or less, and further preferably 20 μm or less. By setting the upper limit to the above range, it is possible to prevent the adhesive layer 11 from deteriorating the step tracking property of the printed layer 3. In addition, the thinning of the obtained laminate 2 becomes possible.

[0147] When manufacturing the laminate 2, as an example, one of the release sheets 12a of the adhesive sheet 1 is peeled off, and the adhesive layer 11 exposed by the adhesive sheet 1 is attached to the surface of the first display component 21 on the side where the printed layer 3 exists. At this time, since the adhesive layer 11 has excellent step tracking properties, the generation of gaps and floating near the step caused by the printed layer 3 can be suppressed.

[0148] Then, another release sheet 12b is peeled off from the adhesive layer 11 of the adhesive sheet 1, and the exposed adhesive layer 11 of the adhesive sheet 1 is bonded to the second display component 22 to obtain a laminate 2. In addition, as another example, the bonding order of the first display component 21 and the second display component 22 may be changed.

[0149] When the laminate 2 is obtained in the above manner, a heat press treatment may be performed to make the adhesive layer 11 adhere closely to the first display component 21 and the second display component 22. Since the adhesive layer 11 has excellent step followability, bubbles and floating near the step can be suppressed even at this stage. In addition, since the adhesive layer 11 also has excellent suppression of optical unevenness, optical unevenness can also be suppressed near the step.

[0150] The autoclave treatment may be performed by a conventional method, and is preferably performed at a temperature of 40 to 80° C. and a pressure of 0.3 to 1 MPa for 5 to 60 minutes.

[0151] In the above-mentioned laminated body 2, since the adhesive layer 11 has excellent step tracking properties, even when the laminated body 2 is placed under high temperature and high humidity conditions (e.g., 85° C., 85% RH, 96 hours), the generation of bubbles, floating, peeling, etc. near the step can be suppressed. In addition, since the adhesive layer 11 also has excellent optical unevenness suppression properties, the generation of optical unevenness near the step can also be suppressed.

[0152] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above embodiments also includes all design changes and equivalents within the technical scope of the present invention.

[0153] For example, any one or both of the release sheets 12a and 12b in the adhesive sheet 1 may be omitted, and in addition, the required optical components may be laminated to replace the release sheets 12a and / or 12b. In addition, the first display component 21 may not have the printed layer 3 (step difference), or may have a step difference other than the printed layer 3. Furthermore, not only the first display component 21, but also the second display component 22 may have a step difference on the adhesive layer 11 side.

[0154] Example

[0155] Hereinafter, the present invention will be described in more detail with reference to Examples and the like; however, the scope of the present invention is not limited to these Examples and the like.

[0156] [Example 1]

[0157] 1. Preparation of (meth)acrylate polymer (A)

[0158] By solution polymerization, 84 parts by mass of n-butyl acrylate, 15 parts by mass of methyl methacrylate (2-oxo-1,3-dioxolan-4-yl) as an ethylene carbonate-containing monomer, and 1 part by mass of 4-hydroxybutyl acrylate were copolymerized to prepare a (meth)acrylate polymer (A). The molecular weight of the (meth)acrylate polymer (A) was measured by the method described below, and the weight average molecular weight (Mw) was 750,000.

[0159] 2. Preparation of adhesive composition

[0160] 100 parts by mass (solid content conversion value; the same below) of the (meth)acrylate polymer (A) obtained in the above step 1 and 0.5 parts by mass of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) diluted with methyl ethyl ketone as the ionic compound (B) were mixed, stirred sufficiently, and diluted with methyl ethyl ketone to obtain a coating solution of an adhesive composition. In addition, the above LiTFSI was diluted with methyl ethyl ketone to a solid content concentration of 10% by mass before being blended.

[0161] 3. Manufacturing of adhesive sheet

[0162] The coating solution of the obtained adhesive composition was applied to the release-treated surface of a heavy-release release sheet (manufactured by LINTEC Corporation, product name "SP-PET382150") obtained by release-treating one side of a polyethylene terephthalate film with a silicone release agent using a knife coater. Then, the coating layer was heated at 90° C. for 1 minute to form an adhesive layer.

[0163] Next, the adhesive layer on the heavy-peel release sheet obtained above and the light-peel release sheet (manufactured by LINTEC Corporation, product name "SP-PET381130") obtained by peeling off one side of a polyethylene terephthalate film using a silicone release agent are laminated together in such a way that the peeling-treated surface of the light-peel release sheet is in contact with the adhesive layer, thereby producing an adhesive sheet having an adhesive layer with a thickness of 25 μm, that is, an adhesive sheet consisting of a structure of heavy-peel release sheet / adhesive layer (thickness: 25 μm) / light-peel release sheet.

[0164] The thickness of the adhesive layer is a value measured using a constant pressure thickness gauge (manufactured by Teclock, product name “PG-02”) in accordance with JIS K7130.

[0165] Here, each compounding ratio (solid content conversion value) of the adhesive composition when the (meth)acrylate polymer (A) is 100 parts by mass (solid content conversion value) is shown in Table 1. In addition, the details of the abbreviations and the like described in Table 1 are as follows.

[0166] [(Meth)acrylate polymer (A)]

[0167] BA: n-butyl acrylate

[0168] CARBOM: 2-oxo-1,3-dioxolan-4-yl methyl methacrylate

[0169] 4HBA: 4-Hydroxybutyl acrylate

[0170] [Ionic compound (B)]

[0171] Lithium bis(trifluoromethylsulfonyl)imide (LiTFSI)

[0172] [Crosslinking agent]

[0173] Trimethylolpropane-modified xylylene diisocyanate (manufactured by Soken Chemical & Engineering Co., Ltd., product name "TD-75")

[0174] [Comparative Examples 1, 3]

[0175] An adhesive sheet was produced in the same manner as in Example 1 except that the types and ratios of the monomers constituting the (meth)acrylate polymer (A) and the amount of the ionic compound (B) added were changed as shown in Table 1.

[0176] [Comparative Example 2]

[0177] 100 parts by mass of the (meth)acrylate polymer (A) obtained in step 1 of Example 1 and 0.22 parts by mass of trimethylolpropane-modified xylylene diisocyanate (manufactured by Soken Chemical & Engineering Co., Ltd., product name "TD-75") as a crosslinking agent were mixed, stirred thoroughly, and diluted with methyl ethyl ketone to obtain a coating solution of an adhesive composition.

[0178] The coating solution of the obtained adhesive composition was applied to the release-treated surface of a heavy-release release sheet (manufactured by LINTEC Corporation, product name "SP-PET382150") obtained by release-treating one side of a polyethylene terephthalate film with a silicone release agent using a knife coater. Then, the coating layer was heated at 90° C. for 1 minute to form a coating layer.

[0179] Next, the coating layer on the heavy-peel release sheet obtained above and the light-peel release sheet (manufactured by LINTEC Corporation, product name "SP-PET381130") obtained by peeling off one side of a polyethylene terephthalate film using a silicone release agent were laminated together in such a way that the peeling-treated surface of the light-peel release sheet was in contact with the coating layer, and cured at 23°C and 50% RH for 7 days to produce an adhesive sheet having an adhesive layer with a thickness of 25 μm, i.e., an adhesive sheet having a structure of heavy-peel release sheet / adhesive layer (thickness: 25 μm) / light-peel release sheet.

[0180] [Comparative Examples 4 to 5]

[0181] An adhesive sheet was produced in the same manner as in Comparative Example 2 except that the types and ratios of the monomers constituting the (meth)acrylate polymer (A) and the amount of the ionic compound (B) added were changed as shown in Table 1.

[0182] The weight average molecular weight (Mw) is a polystyrene-equivalent weight average molecular weight measured using gel permeation chromatography (GPC) under the following conditions (GPC measurement).

[0183] <Measurement conditions>

[0184] ·GPC measuring apparatus: HLC-8020 manufactured by TOSOH CORPORATION

[0185] ·GPC columns (passed in the following order): manufactured by TOSOH CORPORATION

[0186] TSK guard column HXL-H

[0187] TSK gel GMHXL (×2)

[0188] TSK gel G2000HXL

[0189] ·Test solvent: tetrahydrofuran

[0190] ·Measurement temperature: 40℃

[0191] [Test Example 1] (Measurement of gel fraction)

[0192] The adhesive sheets prepared in the examples and comparative examples were cut into a size of 80 mm x 80 mm, and the adhesive layer was wrapped in a polyester net (mesh size 200), and the mass was weighed using a precision balance, and the mass of the adhesive itself was calculated by subtracting the mass of the net alone. The mass at this time was recorded as M1.

[0193] Next, at room temperature (23°C), the adhesive wrapped in the polyester net is immersed in ethyl acetate for 24 hours. Then, the adhesive is taken out and air-dried for 24 hours in an environment of 23°C and 50% relative humidity, and further dried in an oven at 80°C for 12 hours. After drying, the mass is weighed using a precision balance, and the mass of the net alone is subtracted to calculate the mass of the adhesive itself. The mass at this time is recorded as M2. The gel fraction (%) is expressed as (M2 / M1)×100.

[0194] The gel fraction of the adhesive was derived from this. The results are shown in Table 2.

[0195] [Test Example 2] (Measurement of storage modulus)

[0196] The adhesive layers of the adhesive sheets prepared in Examples and Comparative Examples were stacked to a thickness of 0.8 mm to form a laminate. A cylinder with a diameter of 8 mm (height 0.8 mm) was punched out from the obtained laminate of adhesive layers to prepare a sample.

[0197] The samples were tested for dynamic viscoelasticity by a torsional shear method using a viscoelasticity measuring apparatus (manufactured by Anton Paar, product name "MCR302") in accordance with JIS K7244-1 under the following conditions to measure storage modulus (G') (MPa) at 25°C, 50°C and 85°C. The results are shown in Table 2.

[0198] Measuring frequency: 1Hz

[0199] Measuring temperature range: -20℃~150℃

[0200] Heating rate: 3℃ / min

[0201] [Test Example 3] (Measurement of relaxation modulus change value)

[0202] The adhesive layers of the adhesive sheets prepared in the examples and comparative examples were stacked to prepare a laminate having a thickness of 0.8 mm. A cylinder having a diameter of 8 mm (height of 0.8 mm) was punched out from the obtained laminate of adhesive layers and used as a sample.

[0203] For the above sample, according to JIS K7244-1, a viscoelasticity measuring device (manufactured by Anton Paar, product name "MCR302") was used to continuously strain the adhesive by 10% under the following conditions to measure the relaxation modulus G(t) (MPa). Based on the measurement results, the maximum relaxation modulus G(t) was derived. max (MPa), and derive the maximum relaxation modulus G(t) from the measurement max Minimum relaxation modulus G(t) measured from the start to 3757 seconds latermin (MPa).

[0204] Measurement temperature: 25℃

[0205] Measurement points: 1000 points (logarithmic coordinate graph)

[0206] According to the obtained maximum relaxation modulus G(t) max (MPa) and minimum relaxation modulus G(t) min (MPa), and the relaxation modulus change value ΔlogG(t) was calculated based on the following formula (X). The results are shown in Table 2.

[0207] ΔlogG(t)=logG(t) max -logG(t) min …(X)

[0208] [Test Example 4] (Measurement of strain amount)

[0209] The adhesive layers of the adhesive sheets prepared in Examples and Comparative Examples were stacked to prepare a laminate having a thickness of 0.2 mm. A 15 mm x 15 mm rectangular parallelepiped (height 0.2 mm) was punched out from the obtained laminate of adhesive layers to prepare a sample.

[0210] The sample was subjected to constant stress under the following conditions using a viscoelasticity measuring apparatus (manufactured by Anton Paar, product name "MCR302") in accordance with JIS K7244-1, and the strain (%) was measured 1210 seconds after the stress was applied. The results are shown in Table 2.

[0211] Measurement temperature: 25℃

[0212] Measurement points: 321 points

[0213] Stress: 7950Pa

[0214] [Test Example 5] (Measurement of Adhesion Strength)

[0215] The light peeling release sheet is peeled off from the adhesive sheet prepared in the embodiment and the comparative example, and the exposed adhesive layer is bonded to the easy adhesive layer of the polyethylene terephthalate (PET) film (manufactured by TOYOBO CO., LTD., product name "PET TA063", thickness: 100 μm) having an easy adhesive layer to obtain a laminate of a heavy peeling release sheet / adhesive layer / PET film. In addition, regarding comparative example 3, when manufacturing the adhesive sheet, a light peeling release sheet is not used, and an adhesive sheet consisting of a heavy peeling release sheet / adhesive layer (thickness: 25 μm) is prepared, and the exposed adhesive layer is bonded to the easy adhesive layer of the PET film (manufactured by TOYOBO CO., LTD., product name "PET TA063", thickness: 100 μm) having an easy adhesive layer to obtain a laminate of a heavy peeling release sheet / adhesive layer / PET film. The laminate obtained in the above manner is cut into 25 mm wide and 100 mm long.

[0216] Under the environment of 23 ℃, 50%RH, peel off the heavy peeling type release sheet from the above-mentioned laminate, attach the exposed adhesive layer to the following two adherends, use the autoclave manufactured by KURIHARA SEISAKUSHO Co., Ltd., pressurize for 20 minutes at 0.5MPa and 50 ℃. Then, after being placed for 24 hours under the conditions of 23 ℃, 50%RH, use a tensile testing machine (manufactured by ORIENTEC Co., LTD, TENSILON), the adhesive force (N / 25mm) when the laminate of PET film and adhesive layer is peeled off from the adherend is measured under the conditions of 300mm / min of peeling speed and 180 degrees of peeling angle. The conditions not recorded here are measured according to JIS Z0237:2009. The results are shown in Table 2. In addition, " CF " in the table represents that cohesive failure occurs in the adhesive layer.

[0217] <Adhesive>

[0218] Soda-lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd., product name "soda-lime glass", thickness: 1.1 mm)

[0219] Alkali-free glass plate (manufactured by Nippon Sheet Glass Co., Ltd., product name "Eagle-X", thickness: 1.1 mm)

[0220] [Test Example 6] (Evaluation of operability)

[0221] When the light-peelable release sheet was peeled off from the adhesive sheets prepared in Examples and Comparative Examples, the workability (workability of the adhesive sheet) was evaluated based on the following criteria.

[0222] ○: The light release type release sheet can be easily peeled off, and the pressure-sensitive adhesive layer does not suffer from any of deformation, stringing, and cohesive failure.

[0223] △: Although the adhesive layer was deformed during peeling, neither stringing nor cohesive failure occurred, and the light-peelable release sheet was peelable.

[0224] ×: During peeling, the pressure-sensitive adhesive layer was greatly deformed, or stringing or cohesive failure occurred, so that it was difficult to peel off the light-peelable release sheet.

[0225] [Test Example 7] (Evaluation of step followability)

[0226] UV curable ink (manufactured by Teikoku Printing Inks Mfg. Co., Ltd., product name "POS-911 Black") was screen printed on the surface of a glass plate (manufactured by NSG PRECISION, product name "Corning Glass EAGLE XG", 90 mm in length × 50 mm in width × 0.5 mm in thickness) in a frame shape (outer shape: 90 mm in length × 50 mm in width, 5 mm in width). Then, ultraviolet rays (80 W / cm 2 , 2 metal halide lamps, lamp height 15 cm, conveyor belt speed 10-15 m / min), the printed ultraviolet curing ink is cured to manufacture a glass plate with steps caused by printing (height of the step: 5 μm, 10 μm, 15 μm).

[0227] From the adhesive sheet manufactured in the embodiment and the comparative example, a light peeling type release sheet is peeled off, and the exposed adhesive layer is bonded to the easy-adhesive layer of a polyethylene terephthalate (PET) film (manufactured by TOYOBO CO., LTD., product name "PET TA063", thickness: 100 μm). Next, the heavy peeling type release sheet is peeled off to expose the adhesive layer, and a laminator (manufactured by Fujipla Inc., product name "LPD3214") is used to laminate on each glass plate with a step difference in such a way that the adhesive layer covers the entire printed surface of the frame, and it is used as a sample. At this stage, the step tracking after lamination (just after the completion of the attachment) is evaluated based on the following standards. The results are shown in Table 2.

[0228] <Step followability after lamination>

[0229] A: No bubbles, floating, or peeling were observed near the step.

[0230] B: Bubbles with a diameter of 0.2 mm or less were observed near the step, but floating and peeling were not observed.

[0231] C: Bubbles, floating, and peeling with a diameter larger than 0.2 mm were observed near the step.

[0232] Then, the sample was autoclaved at 50°C and 0.5 MPa for 20 minutes and left at normal pressure, 23°C and 50% RH for 24 hours. At this stage, the step followability after autoclaving (initial step followability) was evaluated based on the following criteria. The results are shown in Table 2.

[0233] <Step followability after autoclave treatment>

[0234] A: No bubbles, floating, or peeling were observed near the step.

[0235] B: Bubbles with a diameter of 0.2 mm or less were observed near the step, but floating and peeling were not observed.

[0236] C: Bubbles, floating, and peeling with a diameter larger than 0.2 mm were observed near the step.

[0237] Next, the sample after the autoclave treatment was stored under high temperature and high humidity conditions of 85°C and 85% RH for 96 hours (durability test), and then taken out to an environment of 23°C and 50% RH. Next, the adhesive layer (especially the vicinity of the step caused by the printed layer) was visually confirmed, and the step tracking performance after the high temperature and high humidity conditions was evaluated based on the following criteria. The results are shown in Table 2.

[0238] <Step followability after high temperature and high humidity conditions>

[0239] A: No bubbles, floating, or peeling were observed near the step.

[0240] B: Bubbles with a diameter of 0.2 mm or less were observed near the step, but floating and peeling were not observed.

[0241] C: Bubbles with a diameter larger than 0.2 mm, floating, or peeling were observed near the step.

[0242] [Test Example 8] (Evaluation of optical unevenness)

[0243] UV curable ink (manufactured by Teikoku Printing Inks Mfg. Co., Ltd., product name "POS-911 Black") was screen printed on the surface of a glass plate (manufactured by NSG PRECISION, product name "Corning Glass EAGLE XG", 90 mm in length × 50 mm in width × 0.5 mm in thickness) in a frame shape (outer shape: 90 mm in length × 50 mm in width, 5 mm in width). Then, ultraviolet rays (80 W / cm 2, 2 metal halide lamps, lamp height 15 cm, conveyor belt speed 10-15 m / min), the printed ultraviolet curing ink is cured to produce a glass plate with steps caused by printing (height of the step: 15 μm).

[0244] From the adhesive sheet manufactured in the embodiment and the comparative example, the light peeling type release sheet is peeled off, and the exposed adhesive layer is bonded to the easy adhesive layer of the polyethylene terephthalate (PET) film (manufactured by TOYOBO CO., LTD., product name "PET TA063", thickness: 100 μm) having an easy adhesive layer. Next, the heavy peeling type release sheet is peeled off to expose the adhesive layer, and a laminator (manufactured by Fujipla Inc., product name "LPD3214") is used to laminate on each glass plate with a step difference in such a way that the adhesive layer covers the entire printed surface of the frame. Then, a heat treatment is performed at 50°C and 0.5MPa for 20 minutes, and it is placed at normal pressure, 23°C, and 50%RH for 24 hours to serve as a sample.

[0245] The vicinity of the step caused by the printed layer was visually observed for the above samples, and the optical unevenness was evaluated based on the following criteria. The results are shown in Table 2. In Comparative Example 2, the vicinity of the step was not sufficiently filled after the autoclave treatment, so it was not evaluated.

[0246] <Whether there is optical unevenness>

[0247] ○: No optical unevenness was observed near the step.

[0248] ×: Optical unevenness was observed near the step.

[0249] In addition, since the comparative example 3 had poor workability and it was difficult to prepare the samples for carrying out the test examples 2, 3, 4 and 7, the test examples 2, 3, 4 and 7 were not carried out.

[0250] [Table 1]

[0251]

[0252]

[0253] According to Table 2, the step followability (initial step followability) of the adhesive sheet manufactured in the embodiment after the autoclave treatment and the step followability after the high temperature and high humidity conditions are excellent, and the inhibition of optical unevenness is also excellent. In addition, the adhesive sheet manufactured in the embodiment has high adhesive force and excellent operability.

[0254] Industrial Applicability

[0255] The adhesive sheet of the present invention can be suitably used for laminating a protective panel having a step difference to a desired display component, for example.

[0256] Description of Reference Numerals

[0257] 1: adhesive sheet; 11: adhesive layer; 12a, 12b: release sheets; 2: laminate; 21: first display body constituent member; 22: second display body constituent member; 3: printed layer.

Claims

1. An adhesive composition, characterized in that It contains a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) contains an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer, [Chemical formula 1] The weight average molecular weight of the (meth)acrylate polymer (A) is 500,000 to 2,000,000. The ionic compound (B) is at least one selected from alkali metal salts, alkaline earth metal salts, nitrogen-containing onium salts, sulfur-containing onium salts and phosphorus-containing onium salts, The content of the ionic compound (B) is 0.1 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A).

2. An adhesive composition, characterized in that It contains a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) contains an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer, [Chemical formula 2] The ethylene carbonate-containing monomer is an acrylate represented by the following formula (2): [Chemical formula 3] The weight average molecular weight of the (meth)acrylate polymer (A) is 100,000 to 2,000,000. The ionic compound (B) is at least one selected from alkali metal salts, alkaline earth metal salts, nitrogen-containing onium salts, sulfur-containing onium salts and phosphorus-containing onium salts, The content of the ionic compound (B) is 0.1 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A).

3. An adhesive composition, characterized in that It contains a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) contains an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer, [Chemical formula 4] The ethylene carbonate-containing monomer is a methacrylate represented by the following formula (3): [Chemical formula 5] The weight average molecular weight of the (meth)acrylate polymer (A) is 100,000 to 2,000,000. The ionic compound (B) is at least one selected from alkali metal salts, alkaline earth metal salts, nitrogen-containing onium salts, sulfur-containing onium salts and phosphorus-containing onium salts, The content of the ionic compound (B) is 0.1 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A).

4. The adhesive composition according to any one of claims 1 to 3, characterized in that: The (meth)acrylate polymer (A) contains 0.5% by mass or more and 40% by mass or less of the ethylene carbonate-containing monomer as a monomer unit constituting the polymer.

5. The adhesive composition according to any one of claims 1 to 3, characterized in that: The ionic compound (B) is an alkali metal salt.

6. The adhesive composition according to any one of claims 1 to 3, characterized in that: The content of the crosslinking agent in the adhesive composition is 0.1 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A). 7 . An adhesive prepared by cross-linking the adhesive composition according to claim 1 .

8. An adhesive sheet comprising at least an adhesive layer, characterized in that: The adhesive layer is composed of the adhesive according to claim 7.

9. An adhesive sheet comprising at least an adhesive layer, characterized in that: The adhesive layer is composed of an adhesive formed by cross-linking an adhesive composition. The adhesive composition comprises a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) comprises an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer, [Chemical formula 6] The pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a strain amount of 50% or more and 260% or less 1210 seconds after a stress of 7950 Pa is applied to the pressure-sensitive adhesive at 25° C., For the adhesive constituting the adhesive layer, the maximum relaxation modulus value measured when the adhesive is subjected to 10% strain in accordance with JIS K7244-1 is defined as the maximum relaxation modulus G(t). max MPa, from the measurement to the maximum relaxation modulus G(t) max The adhesive was continuously strained by 10% from the beginning until 3757 seconds later, and the minimum relaxation modulus value measured during this period was defined as the minimum relaxation modulus G(t). min MPa, the relaxation modulus change value ΔlogG(t) calculated by the following formula (X) is 1.2 or more and 2.0 or less, ΔlogG(t)=logG(t) max -logG(t) min …(X), The weight average molecular weight of the (meth)acrylate polymer (A) is 100,000 to 2,000,000. The ionic compound (B) is at least one selected from alkali metal salts, alkaline earth metal salts, nitrogen-containing onium salts, sulfur-containing onium salts and phosphorus-containing onium salts, The content of the ionic compound (B) in the adhesive composition is 0.1 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A).

10. An adhesive sheet comprising at least an adhesive layer, characterized in that: The adhesive layer is composed of an adhesive formed by cross-linking an adhesive composition. The adhesive composition comprises a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) comprises an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer, [Chemical formula 7] The gel fraction of the adhesive constituting the adhesive layer is 0% or more and 60% or less, The weight average molecular weight of the (meth)acrylate polymer (A) is 100,000 to 2,000,000. The ionic compound (B) is at least one selected from alkali metal salts, alkaline earth metal salts, nitrogen-containing onium salts, sulfur-containing onium salts and phosphorus-containing onium salts, The content of the ionic compound (B) in the adhesive composition is 0.1 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A).

11. An adhesive sheet comprising at least an adhesive layer, characterized in that: The adhesive layer is composed of an adhesive formed by cross-linking an adhesive composition. The adhesive composition comprises a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) comprises an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer, [Chemical formula 8] The storage modulus (G') of the adhesive constituting the adhesive layer at 50° C. is 0.01 MPa or more and 1 MPa or less, The weight average molecular weight of the (meth)acrylate polymer (A) is 100,000 to 2,000,000. The ionic compound (B) is at least one selected from alkali metal salts, alkaline earth metal salts, nitrogen-containing onium salts, sulfur-containing onium salts and phosphorus-containing onium salts, The content of the ionic compound (B) in the adhesive composition is 0.1 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A).

12. An adhesive sheet comprising at least an adhesive layer, characterized in that: The adhesive layer is composed of an adhesive formed by cross-linking an adhesive composition. The adhesive composition comprises a (meth)acrylate polymer (A) and an ionic compound (B), wherein the (meth)acrylate polymer (A) comprises an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (1) as a monomer unit constituting the polymer, [Chemical formula 9] The storage modulus (G') of the adhesive constituting the adhesive layer at 25° C. is 0.01 MPa or more and 1 MPa or less, The weight average molecular weight of the (meth)acrylate polymer (A) is 100,000 to 2,000,000. The ionic compound (B) is at least one selected from alkali metal salts, alkaline earth metal salts, nitrogen-containing onium salts, sulfur-containing onium salts and phosphorus-containing onium salts, The content of the ionic compound (B) in the adhesive composition is 0.1 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A).

13. The adhesive sheet according to any one of claims 9 to 12, characterized in that The (meth)acrylate polymer (A) contains 0.5% by mass or more and 40% by mass or less of the ethylene carbonate-containing monomer as a monomer unit constituting the polymer.

14. The adhesive sheet according to any one of claims 9 to 12, characterized in that The ionic compound (B) is an alkali metal salt.

15. The adhesive sheet according to any one of claims 9 to 12, characterized in that The content of the crosslinking agent in the adhesive composition is 0.1 parts by mass or less relative to 100 parts by mass of the (meth)acrylate polymer (A).

16. The adhesive sheet according to any one of claims 9 to 12, characterized in that The adhesive layer has an adhesive force to the soda-lime glass of 1 N / 25 mm or more and 100 N / 25 mm or less.

17. The adhesive sheet according to any one of claims 9 to 12, characterized in that The adhesive sheet includes two release sheets, and the adhesive layer is sandwiched by the release sheets so as to be in contact with release surfaces of the two release sheets.

18. A laminate comprising a display component, another display component, and an adhesive layer for bonding the one display component and the other display component to each other, characterized in that: The adhesive layer is formed of the adhesive layer of the adhesive sheet according to any one of claims 9 to 12.

19. The laminate according to claim 18, characterized in that At least one of the one display constituent member and the other display constituent member has a step on a surface on a side to be bonded by the adhesive layer.

Citation Information

Patent Citations

  • Transparent pressure-sensitive adhesive sheet for flat panel display, and flat panel display

    JP2010097070A

  • (METH)acrylic acid copolymer having five-membered cyclic carbonate group and curable resin composition containing the same

    JP2005036081A

  • Pressure sensitive adhesive sheet and laminate

    JP2020015801A